2019
DOI: 10.1039/c8ra09827a
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D encapsulated into metal-surfactant nanocapsules for enhancing biocatalysis in a two-phase system

Abstract: PLD@MSNC transforms a two-phase system into an emulsion phase, and enhances transphosphatidylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Equations ( 4)-( 6) have been successfully used for the correlation of binodal data of IL-based ATPSs [28][29][30], polymer-based ATPSs [31,32], and hydrophilic alcohol-based ATPSs [33,34]. Based on the obtained R 2 and sd a values in Tables 3-5, it can be concluded that equations ( 5)-( 7) are is the experimental mass fraction of the alcohol mixture, w cal i is the corresponding data calculated using equation (5), and "N" represents the number of binodal data points. perfectly suitable for correlating the binodal data of the investigated systems.…”
Section: Phase Behaviors Of the Il-salt Ilatpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equations ( 4)-( 6) have been successfully used for the correlation of binodal data of IL-based ATPSs [28][29][30], polymer-based ATPSs [31,32], and hydrophilic alcohol-based ATPSs [33,34]. Based on the obtained R 2 and sd a values in Tables 3-5, it can be concluded that equations ( 5)-( 7) are is the experimental mass fraction of the alcohol mixture, w cal i is the corresponding data calculated using equation (5), and "N" represents the number of binodal data points. perfectly suitable for correlating the binodal data of the investigated systems.…”
Section: Phase Behaviors Of the Il-salt Ilatpsmentioning
confidence: 99%
“…Since aqueous biphasic systems were proposed by Beijernick in 1896 [3], the aqueous two-phase system (ATPS) as a new technology that is safe and easy to control and has a simple process is now gradually taking the place of traditional organic-water solvent extraction systems. e ATPS is usually composed of two or more polymers, a polymer, and a salt [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…High stirring rate can promote mass transfer in biphasic enzymatic catalysis [47,48]. However, the further increase of stirring rate from 900 to 1000 rpm could result in fracture of the nanocomposite [36,49] and the dissociation of 2-Melm or PLA1, resulting in a significant reduction of catalytic activity. A weakly alkaline environment (pH 8) can promote the catalytic activity of PLA1 and result in higher L-α-GPC yield.…”
Section: Enzymatic Activities Of 2-melm@pla1/msncmentioning
confidence: 99%
“…The enzymeZIF-8 treated with salt ions showed enhanced activity, storage stability, and the ability to resist against trypsin [29]. We have successfully prepared a novel enzyme-metal-surfactant nanocomposite, which demonstrated strong catalytic activity, storage stability, thermal stability, and good reusability in highly polar solvents and deep eutectic solvents [34][35][36]. Under these considerations, we proposed using metal ions and organic surfactants to construct a metal-surfactant nanocomposite capable of simultaneously encapsulating enzymes, followed by subsequent coordinating modification of the nanocomposite with alkalescent 2-Methylimidazole (2-Melm).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The common phospholipases are mainly phospholipase A 1 (PLA 1 ), phospholipase A 2 (PLA 2 ), phospholipase B (PLB), phospholipase C (PLC) and phospholipase D (PLD). [19][20][21][22] Their action sites are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%